Integration of Stakeholders in Dealing with Covid 19: New Normal in Business Life - Bintang Mukhammad Burhanudin Akbar; Yusuf Iskandar; Kurniawan (Nusantara Science and Technology Proceedings, 2020)
The rapid spread of the Covid-19 virus has a significant impact on the economy and business. Indonesia is one of the countries affected by co-19. The case in Indonesia was recorded as starting in mid-February; in March, schools, and offices began to be closed and replaced with all activities carried out at home. Large companies with sound management systems were also affected by the Covid-19 pandemic. Many companies have ceased operational activities due to dependence on raw materials from abroad. The pandemic will last several months or years until the vaccine and the best treatment method are found. The new normalcy has been felt indirectly by the people of Indonesia. This study was conducted by taking the object of the Covid-19 pandemic incident with Indonesia's cases from April to June 2020. The data used are primary and secondary. The method used in this study is descriptive analysis and the soft system method. The new normalcy resulting from the Covid-19 pandemic has a significant impact and is very different from the usual conditions. Decision-makers need to balance the new prevention requirements aimed at the safety of individuals and groups. The government can work with academics to get the risk level coefficient calculation from the new normality.